Global tilt : leading your business through the great economic power shift - Charan, Ram (United States : Crown Business, 2013)
Shares a playbook for how to run a business in an era when economic growth has stagnated and power has shifted to countries outside America, identifying unique opportunities while providing strategies for navigating emerging challenges
Winning in a tilted world -- Understanding the forces causing the tilt -- The South is coming -- Outside-in and future-back : strategy for a tilted world -- Leadership in a tilted world -- The organization in a tilted world -- Making bets on market growth
Includes bibliographical references (pages 309-313) and index.
Koleksi sumbangan Tun Ahmad Sarji Abdul Hamid.
Keywords: Economic development -- Developing countries; International cooperation; Leadership -- Developing countries; Organizational change